Causal effects of gut microbiota on risk of interstitial cystitis: a two-sample Mendelian randomization study - Gao, Jianguo; Shao, Sihai; Shen, Yuefan (Frontiers in Microbiology, 2024)
Background: The correlation between gut microbiota and interstitial cystitis has garnered significant attention in previous studies. Nevertheless, the causal relationship between them remains to be clarified. Methods: Genetic variation serves as a tool in Mendelian randomization analyses, facilitating the inference of causal relationships between exposure factors and disease outcomes. In this study, summary statistics derived from a comprehensive genome-wide association study conducted by the MiBioGen consortium were utilized as exposure factors, while interstitial cystitis data sourced from the GWAS Catalog served as the disease outcome. Then, a twosample Mendelian randomization analysis was performed by applying inverse varianceweighted, MR-Egger, Weighted Median, Simple Mode, and Weighted Mode. In addition, heterogeneity and horizontal pleiotropy were excluded by sensitivity analysis.